• а) (3x−1)(5x+4)−15x2=6
    ​б) (1−2x)(1−3x)=(6x−1)x−4
    в) 5−x(x−3)=(6−x)(x+2)
    г) (x+4)(x+3)=x−(x−2)(2−x)
    РЕШИТЕ УРАВНЕНИЕ

Ответы 1

  • а) (3х-1)(5х+4)-15х2=615х2-5х+12х-4-15х2=67х=6+4х=10/7х=1 3/7б) (1-2х)(1-3х)=(6х-1)х-41-2х-3х+6х2=6х2-х-46х2-2х-3х-6х2=-4-1-5х=-5х=1в) 5-х(х-3)=(6-х)(х+2)5-х2+3х=6х-х2+12-2х-х2+3х-6х+х2+2х=12-5-х=7х=-7г)(х+4)(х+3)=х-(х-2)(2-х)х2+4х+3х+12=х-(2х-4+2х-х2)х2+4х+3х-х+2х+2х-х2=4-1212х=-8х=-2/3
  • Добавить свой ответ

Войти через Google

или

Забыли пароль?

У меня нет аккаунта, я хочу Зарегистрироваться

How much to ban the user?
1 hour 1 day 100 years